Penerapan Teknologi untuk Meningkatkan Daya Saing Petani Sayuran dalam Memenuhi Permintaan Pasar ekspor - Tomy Perdana; Jajang Sauman; Eliana Wulandari; Eddy Renaldy (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2013)
Small vegetables farmers are required to meet the demand of export markets in the aspect of quality, quantity, sustainability, food safety and competitive prices. Small vegetables farmers should increase the integrated capacity of technological, managerial and institutional in order to fulfill export marketdemand. Universitas Padjadjaran had action research program to helping small vegetables farmers to increase their capacities. The action research program included science and technology application for vegetables export which emphasized on protected agriculture and sprinkle irrigation system. The application of these technologies parallel with the assistance of exportmarket access used contract mechanisme, as well as acces to finance. The program had implemented for three years at Pangalengan, the Distric of Bandung, West Java. In the first year, the program focused on farmers collective system development, protected agriculture development using greenhouse and export market acces. The vegetables production planning improvement, further development of protected agriculture and acces to finance were implemented in the second year program. In the last year, the program applied protected agriculture using rain shelter, sprinkle irrigation system development, and acces to finance. This article discusses about how to understand causal relationship and complexity in the program of science and technology aplication in order to fulfill export market demand. Systemthinking with policy structure diagram (stock and flow diagram) had used to understand a structure of causal relationship among variables in the program to helping small vegetables farmers increase their agribusiness capacities.